2018
DOI: 10.1016/j.envexpbot.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Manipulative experiments demonstrate how long-term soil moisture changes alter controls of plant water use

Abstract: Tree transpiration depends on biotic and abiotic factors that might change in the future, including precipitation and soil moisture status. Although short-term sap flux responses to soil moisture and evaporative demand have been the subject of attention before, the relative sensitivity of sap flux to these two factors under long-term changes in soil moisture conditions has rarely been determined experimentally. We tested how long-term artificial change in soil moisture affects the sensitivity of treelevel sap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 75 publications
5
45
1
Order By: Relevance
“…where β 0 is the intercept, β E and β S are the regression coefficients for PET and RSWC, respectively, and ε is the error term assuming a normal distribution. While PET and soil moisture are typically correlated at seasonal and monthly time-scales, they were decoupled at daily time-scales (Pearson's r = 0.03; p = 0.84; see also Grossiord et al, 2018;Novick et al, 2016). Testing a model including an interaction term between PET and RSWC showed this term was not significant for any of the trees, and therefore, this term was not included in (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…where β 0 is the intercept, β E and β S are the regression coefficients for PET and RSWC, respectively, and ε is the error term assuming a normal distribution. While PET and soil moisture are typically correlated at seasonal and monthly time-scales, they were decoupled at daily time-scales (Pearson's r = 0.03; p = 0.84; see also Grossiord et al, 2018;Novick et al, 2016). Testing a model including an interaction term between PET and RSWC showed this term was not significant for any of the trees, and therefore, this term was not included in (1).…”
Section: Discussionmentioning
confidence: 99%
“…We used PET rather than vapour pressure deficit (e.g., Grossiord et al, 2018;Novick et al, 2016;Oren et al, 1999), as PET is a better proxy of the above-ground environmental influence on transpiration. In π tlp values are not reported for Qualea species because the method of determination is not robust for this genus (Maréchaux et al, 2016). addition to humidity, PET accounts for the role of radiation and wind, which are known to have strong effects in tropical rainforests that are often light-limited (Wagner et al, 2016) and somewhat decoupled from the atmosphere (De Kauwe, Medlyn, Knauer, & Williams, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies deal with a sequence of years with above average rainfall, essential in semiarid grassland for seed production of perennial species, seedling establishment, and plant survival (Peters, Yao, Browning, & Rango, 2014). In a precipitation manipulation experiment, Grossiord et al (2017) found that long-term soil-moisture reduction decreased trees response to daily soil-moisture variation whereas increased long-term soil moisture exaggerated the sensitivity of trees to soil water availability, especially at drier conditions. Soil moisture is a noted metric of hydrologic models (Chandler, Seyfried, McNamara, & Hwang, 2017).…”
Section: Introductionmentioning
confidence: 99%